Optimalisasi Skill Marketing terhadap Loyalitas Nasabah di Perbankan Syariah - Zuhrinal M. Nawawi; Maysa Chairani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study employs a qualitative method with a literature review approach to examine how the optimization of marketing skills contributes to enhancing customer loyalty in Islamic banking. Based on a review of various national journals and theoretical references, it was found that personal selling skills, interpersonal communication, understanding of sharia-compliant products, and the ability to build long-term relationships with customers play a significant role in maintaining loyalty. Amidst the competition between digital and conventional banking, Islamic banks are required to prioritize service values aligned with sharia principles and optimize human resource capabilities in delivering educational, solution-oriented, and consistent approaches. Effective marketing skills not only create a positive customer experience but also enhance trust in Islamic financial institutions.